2012
DOI: 10.1111/j.1445-5994.2011.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit experience of haemopoietic stem cell transplant patients

Abstract: Our study found that acute admission of HSCT patients to the ICU is associated with improved survival compared to our previous experience, with organ failure progression a strong predictor of ICU outcome, and specific disease characteristics contributing to long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…In cohorts including only AlloSCT patients, hospital mortality and overall hospital mortality ranged from 77% to 98% and longterm survival ranged from 3% to 10% [22][23][24][25][26][27][28][29] . Similarly, Agarwal et al [30] reported higher ICU mortality rates between 1988-1998 compared to 1998-2008 in a single center. The improvement in ICU outcomes over the last few decades may have been due to improvements in intensive care, HSCT, and patient selection (Table 2).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In cohorts including only AlloSCT patients, hospital mortality and overall hospital mortality ranged from 77% to 98% and longterm survival ranged from 3% to 10% [22][23][24][25][26][27][28][29] . Similarly, Agarwal et al [30] reported higher ICU mortality rates between 1988-1998 compared to 1998-2008 in a single center. The improvement in ICU outcomes over the last few decades may have been due to improvements in intensive care, HSCT, and patient selection (Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…Elevated serum lactate [16] , bilirubin [11] , and blood urea nitrogen [13,18] have been inconsistently found to be associated with worse prognosis. As for the organ function indexes, APACHE Ⅱ was not found to be predictive of ICU outcomes in HSCT population in various studies [10,13,30] except one [31] . In a cohort of 112 patients, Afessa et al [32] did not find APACHE Ⅱ to have prognostic value while they found APACHE Ⅲ to have a moderate discrimination and good calibration in predicting hospital mortality.…”
Section: Patient Functional Status At the Time Of Icu Admissionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is possible that results of single centre studies can be attributed only to the site where the research was conducted due to individual characteristics of that centre not present in other settings. Many studies had long periods of data collection; eleven studies collected data for 10 years or more [31, 37, 42, 45, 48, 50, 51, 5355, 57]. Collecting data over long periods can lead to era bias, where changes in hospital practice and policy, or improved treatments and technologies can affect patient outcomes.…”
Section: Resultsmentioning
confidence: 99%